1998
DOI: 10.1128/mcb.18.6.3212
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclin D1 Kinase Activity Is Associated with E2F-Mediated Inhibition of Cyclin D1 Promoter Activity through E2F and Sp1

Abstract: Coordinated interactions between cyclin-dependent kinases (Cdks), their target "pocket proteins" (the retinoblastoma protein [pRB], p107, and p130), the pocket protein binding E2F-DP complexes, and the Cdk inhibitors regulate orderly cell cycle progression. The cyclin D1 gene encodes a regulatory subunit of the Cdk holoenzymes, which phosphorylate the tumor suppressor pRB, leading to the release of free E2F-1. Overexpression of E2F-1 can induce apoptosis and may either promote or inhibit cellular proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 85 publications
5
146
0
Order By: Relevance
“…Because ChIP assays (Cicatiello et al, 2004) have revealed that E2F factors bind to DNA in a cell cycle progression-related manner, we next performed deletions of the E2F region, and we designed functional assays to test the particular relevance of these transcription factors in controlling the cyclin D1 promoter activity under ZO-2 effect. In accordance with the results found in other cell lines (Watanabe et al, 1998), the deleted distal "E2F" region seemed to contain a silencer element for the cyclin D1 promoter ( Figure 4B). The generation of different constructs where the region surrounding E2F was deleted allowed the detection of a fragment located between nt Ϫ694 and Ϫ550 that is required for attaining the negative response triggered by ZO-2 ( Figure 4B).…”
Section: Zo-2 Repression Is Mediated By a Putative E2f/e Box Located supporting
confidence: 79%
See 2 more Smart Citations
“…Because ChIP assays (Cicatiello et al, 2004) have revealed that E2F factors bind to DNA in a cell cycle progression-related manner, we next performed deletions of the E2F region, and we designed functional assays to test the particular relevance of these transcription factors in controlling the cyclin D1 promoter activity under ZO-2 effect. In accordance with the results found in other cell lines (Watanabe et al, 1998), the deleted distal "E2F" region seemed to contain a silencer element for the cyclin D1 promoter ( Figure 4B). The generation of different constructs where the region surrounding E2F was deleted allowed the detection of a fragment located between nt Ϫ694 and Ϫ550 that is required for attaining the negative response triggered by ZO-2 ( Figure 4B).…”
Section: Zo-2 Repression Is Mediated By a Putative E2f/e Box Located supporting
confidence: 79%
“…Inside the region located between nucleotides (nt) Ϫ737/ Ϫ730 (distal) or between nt Ϫ143/Ϫ133 (proximal), there are elements recognized by the transcription factors of the E2F family (Fukami-Kobayashi and Mitsui, 1998;Watanabe et al, 1998;Cicatiello et al, 2004). Because ChIP assays (Cicatiello et al, 2004) have revealed that E2F factors bind to DNA in a cell cycle progression-related manner, we next performed deletions of the E2F region, and we designed functional assays to test the particular relevance of these transcription factors in controlling the cyclin D1 promoter activity under ZO-2 effect.…”
Section: Zo-2 Repression Is Mediated By a Putative E2f/e Box Located mentioning
confidence: 99%
See 1 more Smart Citation
“…The antibodies used were: cyclin D1 from Neomarkers (Freemont, CA, USA); b-catenin from BD Transduction Laboratories (Franklin Lakes, NJ, USA); ABC b-catenin from Upstate Biotechnology (Lake Placid, NY, USA); HA.11 antibody from Babco (Richmond, CA, USA); and CREB (total and phospho) from Cell Signaling Technology (Beverly, MA, USA). The À1745 human cyclin D1 promoter reporter construct containing 1745 bp upstream of the transcription initiation site, À1745 CD1-luc (TCF mutant), À1745 CD1-luc (CRE mutant), À66 CD1-luc (without the TCF sites) and the empty luciferase vector pA3-luc have been described elsewhere (Joyce et al, 1999;Watanabe et al, 1998). The pGL3OT and pGL3OF reporter constructs were from Dr Bert Vogelstein (He et al, 1998), the pCRE-luc reporter construct was from Stratagene, HAepitope-tagged wild-type b-catenin construct from Dr Stephen Byers (Orford et al, 1997), the wild-type CREB construct from Dr Marc Montminy (Du et al, 2000), the KCREB construct from Dr Richard Goodman (Walton et al, 1992), the pHYTCAxin-myc clone containing the mouse axin cDNA was from Dr Roel Nusse (Willert et al, 1999) and the dnTCF4 cDNA clone was from Dr Hans C Clevers (Korinek et al, 1997).…”
Section: Reagents and Plasmidsmentioning
confidence: 99%
“…Cell cycle progression is regulated by the coordinated interactions of a variety of proteins, which include E2F-1, cyclin-dependent kinases (Cdks), cyclin E, and p27 kip1 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The retinoblastoma protein (pRb) in its active, hypophosphorylated state is an inhibitor of cell cycle progression from G 1 to S phase (4,6).…”
mentioning
confidence: 99%